More new publications from CTA 2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
More new publications from CTAPriority information themes for ACP agriculture, Proceedings of a CTA seminar 1997.ISBN 92 9081 1692, CTA number 849, 20 Credit points. Policy-makers and planners are the main target groups of this publication.